2021
DOI: 10.1038/s41366-021-00890-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sleep phase and body weight of mobile health App users during COVID-19 mild lockdown in Japan

Abstract: Objective and method The stay-at-home order during the COVID-19 pandemic has restricted individuals’ social behaviors, and therefore, effected their lifestyle including sleep, diet, and physical activity. Using the cross-sectional study design with a large sample size (N = 30,275) from the mobile health App users in Japan, we show age-dependent lifestyle changes during a nonpunitive “mild lockdown” (from April to May 2020). Results Sleep onset and offset w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…As a result, more people crossed borders of prefectures than during the first declaration, including those commuting between prefectures. In contrast to lockdown in Scotland, restrictions in Japan were requested rather than enforced , with no penalties resulting from violations (e.g., Tahara et al, 2021 ). Therefore, to what extent employers and business owners, and citizens followed the state of emergency depended on populations, economic situations of each institution, and individual beliefs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, more people crossed borders of prefectures than during the first declaration, including those commuting between prefectures. In contrast to lockdown in Scotland, restrictions in Japan were requested rather than enforced , with no penalties resulting from violations (e.g., Tahara et al, 2021 ). Therefore, to what extent employers and business owners, and citizens followed the state of emergency depended on populations, economic situations of each institution, and individual beliefs.…”
Section: Methodsmentioning
confidence: 99%
“…Across a larger sample from the same population, Janssen et al (2020) found that participants’ hours of sleep generally increased during the strictest months of lockdown and decreased again when lockdown began to ease. Sleep duration was reported to have lengthened during mild lockdown in Japan ( Tahara et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies across numerous countries reported a worsening of sleep quality, increasing sleep problems, or increasing problems with insomnia during quarantine conditions (Blume et al, 2020;Peretti-Watel et al, 2020;Pinto et al, 2020;Voitsidis et al, 2020;AlRasheed et al, 2021;Cellini et al, 2021;Conte et al, 2021;Hisler and Twenge, 2021;Hyun et al, 2021;Marelli et al, 2021;Martínez-de-Quel et al, 2021;Robillard et al, 2021). However, some studies found that sleep quality did not worsen across all participants (Benham, 2020;Gao and Scullin, 2020;Kocevska et al, 2020;Tahara et al, 2021). Of these studies, a common trend was that younger people or college students reported less sleep problems during the quarantine (Benham, 2020;Tahara et al, 2021).…”
Section: Primary Studiesmentioning
confidence: 99%
“…However, some studies found that sleep quality did not worsen across all participants (Benham, 2020;Gao and Scullin, 2020;Kocevska et al, 2020;Tahara et al, 2021). Of these studies, a common trend was that younger people or college students reported less sleep problems during the quarantine (Benham, 2020;Tahara et al, 2021).…”
Section: Primary Studiesmentioning
confidence: 99%
See 1 more Smart Citation